Seasonal variation of sound production in the Lusitanian toadfish Halobatrachus didactylus - Amorim, Maria Clara Pessoa (2013)
Seasonal variation of sound production, which includes boatwhistles, grunts, croaks and double croaks, was studied in the Lusitanian toadfish Halobatrachus didactylus. Boatwhistles were emitted during the mating season in contrast with the other sound types, which were emitted all year round.